2022
DOI: 10.1108/imds-10-2021-0621
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence enabled robots for stay experience in the hospitality industry in a smart city

Abstract: PurposeThe hospitality industry has witnessed numerous changes to enhance the stay experience of guests. To offer a memorable stay experience, the industry has started deploying intelligent robots. Therefore, this case study aims to examine and explore artificial intelligence (AI) enabled robots in hospitality industry in order to enhance guest experience in a smart city.Design/methodology/approachSemistructured interviews have been conducted at Novotel Ambassador Seoul Dongdaemun Hotels and Residences, Seoul,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 39 publications
(123 reference statements)
0
18
0
Order By: Relevance
“…In addition, Hwang et al (2021aHwang et al ( , 2021b observed that the consumers' perception of utilitarian value had a stronger impact on memorable brand experience when robot baristas provided services compared to human baristas. Lastly, Gupta et al (2022) explored artificial intelligence-enabled robots in smart city hotels and confirmed the role of robot services regarding strengthening the consumers' experience. It can be concluded that robot services play a role in enhancing memorable experiences, which is based on the results of the previous studies, but there is no research about memorable experiences in the field of robotic restaurants.…”
Section: Introductionmentioning
confidence: 92%
“…In addition, Hwang et al (2021aHwang et al ( , 2021b observed that the consumers' perception of utilitarian value had a stronger impact on memorable brand experience when robot baristas provided services compared to human baristas. Lastly, Gupta et al (2022) explored artificial intelligence-enabled robots in smart city hotels and confirmed the role of robot services regarding strengthening the consumers' experience. It can be concluded that robot services play a role in enhancing memorable experiences, which is based on the results of the previous studies, but there is no research about memorable experiences in the field of robotic restaurants.…”
Section: Introductionmentioning
confidence: 92%
“…The application of AI to the customer market has completely changed customer behaviors (Belanche et al, 2019;Gupta et al, 2022). For example, AI can assist customers to solve technical problems and acquire product-related information and price optimization (Adam et al, 2021;Pillai et al, 2020).…”
Section: Literature Review 21 Artificial Intelligencementioning
confidence: 99%
“…The application of AI to the customer market has completely changed customer behaviors (Belanche et al. , 2019; Gupta et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations